Murine Broadly Reactive Antineuraminidase Monoclonal Antibodies Protect Mice from Recent Influenza B Virus Isolates and Partially Inhibit Virus Transmission in the Guinea Pig Model - Tan, Jessica; Chromikova, Veronika; O'Dell, George; Sordillo, Emilia Mia; Simon, Viviana; van Bakel, Harm; Krammer, Florian; McMahon, Meagan (mSphere, 2022)
The global health burden of influenza B viruses, especially in children, has long been underappreciated. Although two antigenically distinct influenza B virus lineages cocirculated before the coronavirus disease 2019 (COVID-19) pandemic, the commonly used trivalent seasonal vaccines contain antigens from only one influenza B virus, providing limited cross-protection against viruses of the other lineage. Current influenza virus vaccines and antivirals have limitations, some of which disproportionately affect their utilization against influenza B viruses. To inform ongoing efforts to address the considerable global burden of influenza B viruses, we previously described five murine monoclonal antibodies that broadly bind conserved epitopes on the neuraminidase of influenza B viruses and protect against lethal challenge in a mouse model when delivered via intraperitoneal injection. Here, we validate the continued relevance of these antibodies by demonstrating that their protective effects extend to lethal challenge with mouse-adapted influenza B viruses recently isolated from humans. We also found that humanization of murine antibodies 1F2 and 4F11 resulted in molecules that retain the ability to protect mice from lethal challenge when administered prophylactically. Intranasal administration as an alternative route of 1F2 delivery revealed no differences in the mouse challenge model compared to intraperitoneal injection, supporting further assessment of this more targeted and convenient administration method. Lastly, we evaluated the potential for intranasal 1F2 administration initiated 1 day after infection to prevent transmission of an influenza B virus between cocaged guinea pigs. Here, we observed a 40% rate of transmission with the 1F2 antibody administered to the infected donor compared to 100% transmission with administration of an irrelevant control antibody. These data suggest that intranasal administration could be a viable route of administration for antibody therapeutics. Collectively, these findings demonstrate the potential of broad antineuraminidase antibodies as therapeutics to prevent and treat infections caused by influenza B viruses. IMPORTANCE The global health burden of influenza B viruses, especially in children, has long been underappreciated. Although two antigenically distinct influenza B virus lineages cocirculated before the coronavirus disease 2019 (COVID-19) pandemic, the commonly used trivalent seasonal vaccines contain antigens from only one influenza B virus, providing limited cross-protection against viruses of the other lineage. Additionally, studies have called into question the clinical effectiveness of the neuraminidase inhibitors that comprise the majority of available antivirals in treating influenza B virus infections. We previously described antibodies that bind broadly to neuraminidases of influenza B viruses across decades of antigenic evolution and potently protect mice against lethal challenge. Here we appraise additional factors to develop these antineuraminidase antibodies as antivirals to prevent and treat infections caused by an extensive range of influenza B viruses. In addition this work assesses recent clinical isolates belonging to the two influenza B virus lineages, finding evidence supporting the development of these antibodies for prophylactic and therapeutic use.